Implementation of Psychoeducation on Marriage Readiness for Asca Elpida's Instagram Followers - Hikmah, Alsarabibah Leli; Sholichah, Ima Fitri (Universitas Negeri Medan, 2025)
The increasing divorce rate in Indonesia shows that many couples are not psychologically ready before getting married. To address this, Asca Elpida developed a social media-based marriage readiness psychoeducation program, especially Instagram, as a preventive measure that is easily accessible to the young generation of early adulthood (18–24 years). Before the implementation, a poll was conducted via Instagram Story which showed that 54% of respondents chose the topic “marriage readiness” as the most popular. This program presents three educational materials in a visual-interactive format and opens up a discussion space via direct message. Evaluation using the Kirkpatrick model at the reaction and learning levels showed a positive response from participants: easy-to-understand material (91%), relevant topics (88%), and increased understanding (84%). However, active participation was still low, indicating the phenomenon of lurking behavior. Nevertheless, this program is effective in increasing psychological literacy and marriage readiness, while also reviving Asca Elpida's Instagram account with meaningful educational content. As a development, it is recommended to use a live webinar format, intensive online training, community forums, or counseling assistance to achieve a deeper and more sustainable impact.